International R&D; rivalry and industrial strategy without government commitment - Leahy, D; Neary, J (Blackwell Publishing, 1996)
We examine optimal industrial and trade policies in a series of dynamic oligopoly games in which a home and a foreign firm compete in R&D; and output. Alternative assumptions about the timing of moves and the ability of agents to commit intertemporally are considered. We show that the home export subsidy, R&D; subsidy and welfare are higher when government commitment is credible than in the dynamically consistent equilibrium without commitment. Commitment thus yields welfare gains (though they are small) but so does unanticipated reneging, whereas reneging which is anticipated by firms yields the lowest welfare of all.